Exploring public land's organizational resilience and communication in the context of climate change - Schweizer, Sarah Elizabeth, author; Thompson, Jessica Leigh, advisor; Welling, Leigh, committee member; Klein, Julia, committee member (Colorado State University. Libraries, 2010)
Climate change presents significant ecological and social challenges to natural resource agencies, which are responsible for managing changing landscapes while at the same time communicating the impacts of this phenomenon and associated management responses with an increasingly concerned public audience. In most cases, organizations were not structured to undertake dynamic, interdisciplinary issues, such as climate change and consequently suffer in slow response times and ineffective communication. Due to these challenges this research investigates three separate scales of climate change communication within America's public lands. Research will inform important knowledge gaps pertaining to climate change communication and management in federal land management agencies. The three scales and research perspectives will contribute to a larger investigation, providing multiple insights to a very complex and nuanced challenge of communicating and organizing in an era of rapid environmental change such as climate change.
Department Head: Michael J. Manfredo.